MISINTERPRETATION OF INFLAMMATORY LESION AND BURKITT'S LYMPHOMA IN SWELLING AND TOOTH MOBILITY CASES - Yolanda Kartika Asmarani; Yanuar Kristanto; Annisa Putri (Journal of Health and Dental Sciences, 2023)
Most complaints in dentistry today are about swelling and mobility of the tooth, and the diagnosis of an inflammatory lesion is generally made in both complaints. Burkitt's lymphoma (BL) is a type of malignant tumor classified as Non-Hodgkin's Lymphoma (NHL) with clinical symptoms of swelling dan tooth mobility similar to the inflammatory lesions. This paper aims to describe the similarities between inflammatory lesions and Burkitt's lymphoma. Burkitt's lymphoma can be classified into endemic, sporadic, and human immunodeficiency-related. Sporadic BL (sBL) occurs in approximately 12 to 30% of maxillofacial patients and commonly affects children. Several case studies reported that the clinical symptom of sBL is swelling. It has been reported in Europe and Asia that sBL in children shows swelling and tooth mobility in the maxillary and mandibular regions. Enlargement and redness of gingival tissue, hypermobility of the tooth, and swelling of the gingival around the painful tooth were reported as sBL cases after some examination. Inflammatory lesions such as BL-like have similar clinical symptoms, so the dentist must be careful in diagnosing cases of swelling and tooth mobility. DOI : 10.54052/jhds.v3n1.p69-78